State funded education system in Kazakhstan - Mukhtarova, K.; Myltykbayeva, A. (Journal of Economic Research & Business Administration, 2015)
The paper reveals the need for, the nature and prospects of the development of state funded education system (GONS). The author writes that GONS - a new alternative way to pay and receive state support vocational and higher education, giving everyone the opportunity to systematically collect funds on deposit in banks to pay for the education of their children or relatives in the universities and colleges of Kazakhstan and foreign countries in the future, starting with birth. Difference and advantage of educational accumulative deposits from usual deposits is that on accumulation on this system the state award of five percent will be annually charged, and for socially vulnerable segments of the population – seven annual interest rates, but no more than 100 MSI (161,8 thousand tenges)